Assessment of marine tourism carrying capacity: a case study at Kapas Island Marine Park, Malaysia - Mohd Adam, Syamimi; Mohammad Afandi, Syamsul Herman; Ling, Siow May; Mohd Yusof, Mohd Johari (Human Resource Management Academic Research Society, 2024)
To prohibit marine park tourism destinations from being mistreated, carrying capacity must be appraised and well-organized properly. A crucial fragment of conquering sustainable tourism management and development is the appraisal of the carrying capacity of marine park destinations. The research was conducted at Kapas Island Marine Park (KIMP) in Terengganu, Malaysia. This paper presents physical carrying capacity and real carrying capacity assessment for three selected recreational activities at KIMP. The findings show that hiking at Bukit Singa with a carrying capacity of 22 visitors per day, snorkelling with a carrying capacity of 1368 visitors per day and lastly beach picnic with a carrying capacity of 450 visitors per day. The policy makers might use these real estimations of carrying capacity for recreational activities for providing great tourism experiences among visitors and sustainability of natural resources in the future.